2008
DOI: 10.1038/sj.bjc.6604273
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the efficacy and toxicity of 131I-metaiodobenzylguanidine therapy for metastatic neuroendocrine tumours

Abstract: 131 I-metaiodobenzylguanidine ( 131 I-MIBG) is a licensed palliative treatment for patients with metastatic neuroendocrine tumours. We have retrospectively assessed the consequences of 131 I-MIBG therapy in 48 patients (30 gastroenteropancreatic, 6 pulmonary, 12 unknown primary site) with metastatic neuroendocrine tumours attending Royal Liverpool University Hospital between 1996 and 2006. Mean age at diagnosis was 57.6 years (range 34 -81). 131 I-MIBG was administered on 88 occasions (mean 1.8 treatments, ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 20 publications
(27 reference statements)
3
22
0
Order By: Relevance
“…In agreement with previous reports, hematotoxicity was the primary side effect of 131 I-MIBG therapy in the present study (1,10,(24)(25)(26)34,35); this side effect was noted at a higher frequency (10%-20% perpatient incidence of grade 3 or 4) with the studied treatment regimen than with previously reported treatment regimens with lower single activities (23,24,26,27). However, it was of a transient nature in our cohort and triggered no hospitalization, granulocyte stimulation, or thrombocyte substitution, except in 1 patient with grade 4 thrombocytopenia (cumulative activity of 66.6 GBq).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In agreement with previous reports, hematotoxicity was the primary side effect of 131 I-MIBG therapy in the present study (1,10,(24)(25)(26)34,35); this side effect was noted at a higher frequency (10%-20% perpatient incidence of grade 3 or 4) with the studied treatment regimen than with previously reported treatment regimens with lower single activities (23,24,26,27). However, it was of a transient nature in our cohort and triggered no hospitalization, granulocyte stimulation, or thrombocyte substitution, except in 1 patient with grade 4 thrombocytopenia (cumulative activity of 66.6 GBq).…”
Section: Discussionsupporting
confidence: 82%
“…This finding was particularly encouraging considering the difficulty in controlling carcinoid symptoms, which frequently determine patients' quality of life and increase morbidity rates (22). A morphologic tumor response after 131 I-MIBG therapy, on the other hand, was less frequently observed for carcinoid tumors, with reported response rates of 0%-35% (10,11,(23)(24)(25)(26)(27). The main observed outcome in the present study was disease stabilization (with or without minor remission) in 80%-90% of patients.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…An example of a patient with good uptake on the MIBG imaging scan that went on to have MIBG therapy is demonstrated in Fig 4 . Approximately 40-50% of patients develop good symptomatic response to treatment. [33][34][35] Not many studies evaluated progression-free survival, but most studies showed a median overall survival of over 40 months following MIBG therapy. Interestingly, Sywak et al compared two groups of patients with midgut NETs.…”
Section: Mibg Imaging and Therapymentioning
confidence: 99%
“…Myelodysplasia is another possible rare side effect, which may occur in patients heavily pre-treated with chemotherapy or radiotherapy. [33][34][35] Tumour and critical organ dosimetry Dosimetry is the measurement of absorbed radiation dose imparted by ionising radiation. Dosimetry can be performed both to calculate critical organ radiation dose (to limit toxicity) and to optimise tumour dose.…”
Section: I-mibg Toxicitymentioning
confidence: 99%